Penerapan Metode Pembelajaran Kooperatif TPS Dalam Meningkatkan Hasil Belajar IPS - Gulo, Megaria Murniati (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The purpose of this study was to improve: (1) the activeness of Class IX-A students of SMP Negeri 4 Gunungsitoli Utara in participating in Integrated Social Studies subjects, especially Economics through the TPS cooperative learning model, (2) student achievement of Class IX-A SMP Negeri 4 Gunungsitoli North in participating in Integrated Social Studies subjects, especially Economics through the TPS cooperative learning model. This study uses a classroom action research approach. The subjects of this study were 40 students of class IX-A SMP Negeri 4 Gunungsitoli Utara. This research was conducted in collaboration between researchers, social studies teacher colleagues and involved student participation. The data collection technique was carried out through activities in the form of: (a) observation, (b) interviews, (c) tests. The research procedure includes the following stages: (a) planning the action, (b) implementing the action, (c) observing and interpreting, and (d) analyzing and reflecting. Based on the research results, it can be concluded that: (1) the application of TPS cooperative learning model can increase student activity during learning. (2) the application of the TPS cooperative learning model can improve student achievement Keywords: economy; think pair share Abstrak: Tujuan penelitian ini adalah untuk meningkatkan : (1) keaktifan siswa Kelas IX-A SMP Negeri 4 Gunungsitoli Utara dalam mengikuti mata pelajaran IPS Terpadu khususnya Ekonomi melalui model pembelajaran kooperatif TPS, (2) prestasi siswa Kelas IX-A SMP Negeri 4 Gunungsitoli Utara dalam mengikuti mata pelajaran IPS Terpadu khususnya Ekonomi melalui model pembelajaran kooperatif TPS. Penelitian ini menggunakan pendekatan penelitian tindakan kelas. Subyek penelitian ini adalah siswa Kelas IX-A SMP Negeri 4 Gunungsitoli Utara yang berjumlah 40 siswa. Penelitian ini dilaksanakan dengan kolaborasi antara peneliti, rekan guru IPS dan melibatkan partisipasi siswa. Teknik pengumpulan data dilakukan melalui kegiatan berupa : (a) observasi, (b) wawancara, (c) tes. Prosedur penelitian meliputi tahap : (a) perencanaan tindakan, (b) pelaksanaan tindakan, (c) observasi dan interprestasi, dan (d) analisis dan refleksi. Berdasarkan hasil penelitian dapat disimpulkan: (1) penerapan model pembelajaran kooperatif TPS dapat meningkatkan keaktifan siswa selama pembelajaran. (2) penerapan model pembelajaran kooperatif TPS dapat meningkatkan prestasi belajar siswa Kata Kunci: ekonomi; think pair share